The use of digital classroom and English language learning in third grade students of primary level at De la Inmaculada Jesuitas-Lima School, 2018 - Moreno Agurto, Victor Alejandro (2019)
A digital classroom [DC] is really important in the English language learning process. The DC has technology resources such as tablets and an interactive whiteboard [IWB] which catch students’ attention in order to communicate, write and read in English language [EL]. The purpose of this study was to determine to what extent the use of DC is related to the English language learning [ELL] at De la Inmaculada Jesuitas-Lima school, Surco 2018. Specifically, the study was intended to assess students’English learning through the use of tablets and IWB as technological resources of the DC. In order to achieve the objectives of this study, a descriptive method was used. The data were collected by a questionnaire and a test of English given to one hundred thirteen students of third grade primary level. Based on the collected information through the mentioned instruments and their correspondent analysis and interpretation, the findings of the study indicated that the DC is significantly related the ELL in the participant students.